Module of Cognitive Behavior Play Therapy on Decision Making Skills and Resilience Enhancement (CBPT Module) - Nor Hamizah Ab Razak; Ku Suhaila Ku Johari; Mohd Izwan Mahmud; Nadziroh Md Zubir; Sabihah Johan (Human Resource Management Academic Research Society, 2024)
Gifted and talented students have high intellectual, creativity and problem-solving skills. However, these groups tend to have issues related to social and emotional issues. Decision making skills and resilience are necessary elements in helping these groups deal with the social and emotional issues faced effectively. This study aims to produce a structured module based on Cognitive Behavior Play Therapy by making the Sidek’s Module Development Model as a guide in its development process. The contents of the module are based on critical and analytical literature review. The draft module consists of six sub modules: Movement Therapy, Art Therapy, Clay Therapy, Sand Therapy, Music Therapy and Puppet Therapy. The sub module is broken down into 14 activities and six units. It is proposed that further studies to be conducted to see the validity and reliability of this module.